Balancing Business and Human Rights in ASEAN: A Comparative Study of National Action Plans in Thailand, Indonesia, and Vietnam - Indriana, Dewi; Bernika Ifada Kamila Putri (Center for Law and Responsible Business Studies, 2026)
As ASEAN economies accelerate industrialization, ensuring corporate accountability for human rights becomes increasingly urgent. This study provides a comparative analysis of National Action Plans (NAPs) on Business and Human Rights (BHR) in Thailand, Indonesia, and Vietnam, which are currently the only ASEAN member states to have adopted such frameworks. Drawing on the United Nations Guiding Principles’ “Protect, Respect, Remedy” (PRR) framework, the paper examines how each country’s NAP addresses long-standing implementation gaps identified in the 2013–2014 ASEAN baseline studies. Through document analysis and cross-country comparison, the study identifies areas of convergence, including regulatory reform, stakeholder participation, and institutional anchoring, as well as key divergences in legal architecture, enforcement capacity, and integration with trade and development strategies. While all three NAPs represent normative progress, ongoing challenges related to remedy access, due diligence implementation, and stakeholder engagement highlight the need for greater regulatory coherence. The findings offer actionable insights for ASEAN governments and regional institutions aiming to institutionalize a rights-based approach to business conduct in the context of deepening economic integration.